KEPENTINGAN NASIONAL AUSTRALIA DENGAN MENJADIKAN BALI SEBAGAI DESTINASI WISATA FAVORIT (2018) - Nathalia Monica Kristy; Setyasih Harini; Halifa Haqqi (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
Australia, which is Indonesia's closest neighbor, has more than just business, security and proven political relations with Australians who make Bali their favorite tourist destination. Although the relationship between Australia and Indonesia had experienced ups and downs, it did not make the relationship between the two countries hostile but became even closer to the efforts to resolve the problem. The existence of a Travel Warning issued by the Australian Government because of Indonesia's critical situation did not discourage Australians from visiting Bali, with various efforts made by the Government of Bali to give positive views to Australians. This is proven by the increase in visits every year and the "Australian Family Tourism Awards" given by the Australian media by Bali in 2018 as a favorite tourist destination for Australians in the category of family holidays. The policy of "Good International Citizenship" to achieve Australia's national interests which are security, economy and geopolitics. Multi-Track Diplomacy is a form of maintaining Australia's relationship with Bali. Relationships made through the government or non-government with organizations within it, business carried out by Australians in Indonesia, the media, to the opinions of Australian citizens are ways to keep Bali as the favorite choice of Australians spending time on vacation, doing business, student exchange and culture as well as spending retirement’s time. Key words: Bali, Australia, National Interest, Multi-Track Diplomacy.